A method for preparing a colorful color-changing material

By adopting a composite multi-layer core-shell structure of titanium oxide nanocrystal particles and photochromic compounds in photochromic materials, the problems of single color change and slow response time of existing photochromic materials are solved, and colorful color change and blue light protection are achieved The effect of the application is suitable for a variety of application scenarios.

CN116769461BActive Publication Date: 2024-12-20JIANGSU SHIKE NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310730081.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The existing photochromic materials have single color changes, slow response time, and inorganic color-changing materials have shortcomings in color discoloration efficiency and fatigue resistance, making it difficult to achieve colorful and comprehensive color discoloration and design chromatography adjustments.

Method used

Using titanium oxide nanocrystal particles as the core, photochromic compounds as the intermediate layer, and surfactant as the shell, photochromic nanocomposite microspheres with composite multi-layer core-shell structures are formed. Through the combination of multiple nanocomposite microspheres, the photochromic nanocomposite microspheres are realized. Various reversible color changes under ultraviolet radiation and provide protection in light and dark environments.

Benefits of technology

It has achieved the short color change time, high response sensitivity, rich color changes of colorful color changes, and has good anti-blue light effects. It is suitable for applications such as filters, functional clothing and anti-counterfeiting technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004293999290000021
    Figure BDA0004293999290000021
  • Figure BDA0004293999290000031
    Figure BDA0004293999290000031
  • Figure BDA0004293999290000041
    Figure BDA0004293999290000041
Patent Text Reader

Abstract

A method for preparing a colorful color-changing material, the method comprising: a. preparing a titanium oxide hydrosol; b. adding a photochromic compound to an alcohol solvent to prepare a photochromic color-forming body solution; c. adding the photochromic color-forming body solution to the titanium oxide hydrosol, and adding a surfactant to obtain a titanium oxide nano-microsphere containing a photochromic compound modified by a surfactant ligand. The inner core of the nano-composite microsphere is a titanium oxide nano-crystalline particle, the outer shell is coated with a surfactant, and the photochromic compound is in the middle layer between the inner core and the outer shell, forming a composite multi-layer core-shell structure. The photochromic compound is selected from spiropyran, naphthopyran and spirooxazine compounds. Through the compounding of multiple photochromic compounds and the synergistic effect with titanium oxide nano-crystalline particles, the prepared color-changing material can not only change color under ultraviolet radiation and present a variety of reversible color changes, but also protect against harmful strong light or short-wave blue light in different light and dark environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photochromic materials, and in particular relates to a method for preparing photochromic nanocomposite microspheres. Background Art

[0002] Photochromic materials refer to a type of material that can change color after being stimulated by a light source. They can be divided into two categories: inorganic photochromic materials and organic photochromic materials. Organic photochromic materials have good performance in information storage, optical lenses, textiles and clothing, anti-counterfeiting printing and other fields due to their wide variety and diverse colors. For example, photochromic compounds such as spiropyran, spirooxazine, naphthopyran, and fulgide; while inorganic photochromic materials have the disadvantages of single color change, difficult surface modification, and slow color change response time, but inorganic photochromic materials have good fatigue resistance and thermal stability. Therefore, how to combine the advantages of organic and inorganic materials to form an organic / inorganic hybrid composite material is one of the future research directions of photochromic technology. In addition, the color change of existing color-changing materials can only gradually change from colorless to darker, and its reversible change is basically a process from colored to colorless, and the color change is relatively single. For example: spiropyran photochromics are mostly colorless to red or purple, naphthopyrans are mostly colorless to green, and spirooxazines are mostly colorless to yellow or blue. It is difficult for the same type of photochromic material to achieve colorful and comprehensive color change or to adjust according to the designed color spectrum. The color is relatively single and cannot achieve satisfactory color. Although some use dyes to adjust the color, the transmittance is affected after fading due to the influence of the dyes. Such photochromics are not very practical.

[0003] Photochromic properties are often affected by polymer molecules, other chemical additives, microstructure, polymerization environment, etc. For example, the color-changing compound is greatly affected by the ultraviolet absorber in the polymer. Since the ultraviolet rays are absorbed by the light absorber in the polymer, the color-changing compound is greatly restricted by the ultraviolet spectrum, resulting in low color-changing efficiency. At the same time, the existence of refractive power leads to inconsistent edge thickness and center thickness of the lens. In this case, if the method of adding the color-changing compound to the body is still used, it will lead to color depth and color difference in different places of the lens. Therefore, some domestic manufacturers use spin coating to produce color-changing lenses. The spin coating method is to add the prepared color-changing solution to the spin coater after the substrate is made. After fully mixing, the substrate is fixed on the spin coater for centrifugal rotation and solidified to form a product with a color-changing effect. Compared with the substrate method, the spin coating method has the advantages of high technical content, theoretically any product can be made, and the product color difference is small. The disadvantage is that the color-changing efficiency is not high due to the relatively reduced color-changing coating space, the reduced color-changing space and the change of the external environment temperature. Therefore, developing photochromic coating technology with fast color change response speed and high color accuracy is an important development direction in the future. Summary of the invention

[0004] In view of the above problems of the prior art, the present invention provides a photochromic nanocomposite microsphere as a colorful color-changing material, and provides a preparation method thereof. The inner core of the nanocomposite microsphere is a titanium oxide nanocrystalline particle, the outer shell is coated with a surfactant, and the photochromic compound is in the middle layer between the inner core and the outer shell to form a composite multilayer core-shell structure. The photochromic compound is selected from spiropyran, naphthopyran and spirooxazine compounds. By compounding a variety of nanocomposite microspheres, the prepared color-changing material can not only change color under ultraviolet radiation, but also present a variety of reversible color changes. At the same time, the titanium oxide nano and the photochromic compound work synergistically to protect against harmful strong light or short-wave blue light in different light and dark environments. The photochromic material has the advantages of short color change time, high response sensitivity, rich color changes, and good blue light protection effect.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a colorful color-changing material, the method comprising the following steps:

[0007] a. Preparation of titanium oxide hydrosol:

[0008] Adding H2SO4 aqueous solution to a 0.1-1 mol / L soluble titanium salt aqueous solution until the solution becomes transparent, then adding 15-30 wt% NaOH aqueous solution with a pH value between 7 and 11, and gradually precipitating; heating to 30°-70°C, adding acid to dissolve the precipitate, and the pH value is between 4 and 7 to obtain titanium oxide hydrosol;

[0009] b. Preparation of photochromic color former solution:

[0010] Adding the photochromic compound into an alcohol solvent, the photochromic compound and the solvent are prepared in a mass ratio of 1:(50-120) to obtain a photochromic color-forming body solution;

[0011] The color-changing compound is selected from one of the following compounds:

[0012]

[0013]

[0014] c. Preparation of core-shell photochromic nanocomposite microspheres:

[0015] The photochromic color-forming body solution prepared in step b is added to the titanium oxide hydrosol, and a surfactant is added, wherein the mass ratio of the photochromic compound, the soluble titanium salt and the surfactant is 1:(5-17):(0.5-0.9), and the mixture is stirred for 20-40 minutes, cooled to room temperature, and the reaction solution is separated and precipitated. The precipitate is collected by filtration, washed, and dried to obtain titanium oxide nanoparticles containing photochromic compounds modified by surfactant ligands.

[0016] During the entire reaction process, TiO2 crystal nuclei are obtained through aqueous phase synthesis, and as the nanocrystal nuclei gradually aggregate, secondary particles, namely titanium oxide nanospheres, are formed; since such titanium oxide nanospheres have a larger specific surface area and a higher surface energy, the subsequently added photochromic compounds are adsorbed on the surface or gaps of the TiO2 spheres in the form of nanoparticles to achieve photosensitization modification; with the addition of surfactants, the surface tension and critical micelle concentration of the solution system are changed, the nucleation of the nanocrystals is gradually terminated, and the surfactants combine with the central atomic titanium metal by coordination bonds to form complex coordination units that are coated around the nanocrystal cores, thereby forming a three-layer core-shell structure of TiO2 / color former / ligand.

[0017] In the preparation method as described above, preferably, the soluble titanium salt is one of titanium dichloride, titanium tetrachloride, titanium sulfite and titanyl sulfate.

[0018] In the preparation method as described above, preferably, the surfactant is at least one of stearic acid, alkyl glucoside, sodium dodecylbenzene sulfonate, fatty acid glyceride, polysorbate, lauroyl glutamic acid, thioglycolic acid, mercaptopropionic acid and α-mercaptoglycerol.

[0019] In the preparation method as described above, preferably, the solvent is at least one of methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, and hexylene glycol.

[0020] In the preparation method as described above, preferably, the solvent is at least one of methanol, ethanol and isopropanol.

[0021] In a preferred embodiment of the present invention, the spirooxazine photochromic compound (IV) is synthesized by the following method, but is not limited to the following method:

[0022] Step 1: Mix the cyanide aqueous solution with the alcohol solution of Acid Orange II, control the temperature at 80-90°C for 15-42 hours under stirring, pass CO2 gas to saturation, collect the precipitated yellow precipitate after filtration, and then dissolve the collected crude product with an appropriate amount of ethanol at room temperature, add a small amount of attapulgite adsorbent to the filtrate, filter the insoluble matter after sufficient stirring, add excess water to the ethanol solution, and precipitate the intermediate from the ethanol solution because the intermediate is insoluble in cold water, filter it, and vacuum dry it to obtain a relatively pure intermediate product.

[0023] The reaction formula is as follows:

[0024]

[0025] Step 2: Take a certain amount of the intermediate, anhydrous calcium sulfate and sodium bicarbonate and add them to a toluene solution of 1,3,3-trimethyl-2-methyleneindoline, then add dimethyl sulfoxide, control the reaction temperature at 70-80°C, react in the dark for 15-24 hours, protect with nitrogen, filter to remove impurities, heat the filtrate to 80-90°C, evaporate to remove the solvent, wash and dry to obtain a colorless cyano spirooxazine photochromic compound.

[0026] The specific reaction formula is as follows:

[0027]

[0028] In the synthesis of the spirooxazine photochromic compound (IV) as described above, preferably, in the step 1, alcohol and water are mixed in a mass ratio of 1:(1-3), and the alcohol is preferably one of methanol, ethanol and propanol.

[0029] In the synthesis of the spirooxazine photochromic compound (IV) as described above, preferably, the cyanide is one of potassium cyanide, sodium cyanide and amine cyanide, and the mass ratio of acid orange II, cyanide and alcohol-water mixed solvent is 1:(2-3):(10-15).

[0030] In the synthesis of the spirooxazine photochromic compound (IV) as described above, preferably, the mass ratio of the intermediate to 1,3,3-trimethyl-2-methyleneindoline is 1:(1-1.5).

[0031] In the synthesis of the spirooxazine photochromic compound (IV) as described above, preferably, the mass ratio of the intermediate, 1,3,3-trimethyl-2-methyleneindoline and toluene is 1:(1-1.5):(20-30).

[0032] In the synthesis of the spirooxazine photochromic compound (IV) as described above, preferably, the mass ratio of dimethyl sulfoxide, sodium bicarbonate, calcium sulfate and the intermediate is (0.6-1.0):(0.9-1.2):(1.5-2.5):1.

[0033] The beneficial effects of the present invention are:

[0034] 1. The colorful color-changing material prepared by the present invention changes color after being irradiated by sunlight / ultraviolet rays, and returns to a colorless state when the sunlight / ultraviolet rays are lost. According to the selection and matching of different types of photochromic compounds, one color change or multiple color changes can be achieved. Since different types of photochromic compounds have different spectral response sensitivities, the color change process and the fading process can present multiple color changes before and after, achieving a variety of color and visual effects, which can meet the application performance requirements of photochromic materials such as filters, functional clothing and anti-counterfeiting technology.

[0035] 2. The colorful color-changing material prepared by the method of the present invention has a three-layer composite core-shell structure, wherein the core is titanium oxide nanospheres, the middle layer is a photochromic layer composed of a color-changing compound, and the outer shell is an anionic surfactant or a non-ionic surfactant. On the one hand, this structure can protect the color-changing compound from external environmental pollution during the processing process by a relatively stable outer shell. On the other hand, by organically modifying the titanium oxide surface, its interfacial compatibility and transparency in organic media are improved.

[0036] 3. The three-dimensional space of the titanium oxide core in the microsphere is within the nanoscale range. The energy level change brought about by the quantum size effect increases the van der Waals area of ​​the color-changing molecule, enhances the activity of the color-changing body, increases the conjugated system, increases the spatial volume of the molecule, and increases the gap between molecules, thereby reducing the conversion barrier between the color-changing open-loop body and the colorless closed-loop body, shortening the conversion time, and accelerating the speed. Existing blue light absorbing materials all absorb ultraviolet rays, and the absorption of ultraviolet rays can affect the photochromic reaction. The titanium oxide nanospheres in the core-shell structure of the present invention are located in the innermost part, and the incident light first excites the color-changing layer. At the same time, the titanium oxide nanospheres in the core have the characteristics of reflecting and scattering ultraviolet rays, so that the irradiation intensity of the ultraviolet rays required to excite the color-changing compound is not affected, and the color-changing effect is good.

[0037] 4. The surface of titanium oxide in the core-shell microspheres is loaded with photochromic compounds, TiO2 is photosensitized, the absorption spectrum is red-shifted, titanium oxide and the color-changing compounds synergistically change the light absorption intensity and wavelength range, and enhance the protection effect of blue light and harmful light. The colorful color-changing filter lens containing photochromic nanocomposite microspheres manufactured by the present invention can not only change color in sunlight, protect against strong light and ultraviolet rays, but also protect against blue light below 435nm indoors, achieving the performance of all-weather protection against ultraviolet rays and short-wave blue light in different light and dark environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The infrared spectrum of the spirooxazine photochromic compound (IV) prepared in a specific embodiment.

[0039] Figure 2This is a transmission electron microscope photograph of the photochromic nanocomposite microspheres prepared in Example 1.

[0040] Figure 3 This is the XRD diffraction pattern of the photochromic nanocomposite microspheres prepared in Example 1.

[0041] Figure 4 This is a comparison spectrum of the multi-color-changing blue light protection lens prepared in Example 1 before and after irradiation.

[0042] Figure 5 This is an absorption spectrum curve of the photochromic nanocomposite microsphere solution prepared in Example 14.

[0043] Figure 6 These are photos of the discoloration and fading process of the photochromic nanocomposite microsphere solution prepared in Example 14. DETAILED DESCRIPTION

[0044] The present invention is further described below by means of specific examples, but this is not intended to limit the protection scope of the present invention.

[0045] Some of the raw materials in the following examples were prepared by the following method:

[0046] 1. Spirooxazine photochromic compounds (IV)

[0047]

[0048] Take 4400 g of KCN and add it to 15000 ml of pure water. Add 2000 g of Acid Orange II in 9000 ml of ethanol solution to the aqueous solution. Heat to 85 ° C and keep warm for 42 hours under stirring. The solution changes from orange-red to dark dark green. Pass CO2 gas to saturation, filter and collect the yellow precipitate, add 1800 g of ethanol to dissolve the collected crude product at room temperature, add 120 g of attapulgite adsorbent to the filtrate, stir well and filter out the insoluble matter, add excess water to the ethanol solution, collect and filter after crystals precipitate, and vacuum dry to obtain the intermediate (SO).

[0049] Take 180g of SO intermediate, 320g of anhydrous calcium sulfate and 180g of sodium bicarbonate, add them to 4650ml of toluene solution of 200g of 1,3,3-trimethyl-2-methyleneindoline, and then add 160ml of dimethyl sulfoxide. The reaction temperature is controlled at 80°C, and the reaction is protected from light for 19 hours. Under N2 protection, impurities are removed by filtration, and the filtrate is heated to 80°C to evaporate the solvent, washed and dried to obtain a cyano spirooxazine photochromic compound (IV).

[0050] Infrared spectrum (FT-IR) test: The spirooxazine powder sample prepared in the above steps was dried in a vacuum oven to constant weight, and about 30 mg was taken out and prepared by KBr tablet method. The infrared spectrum was measured by Fourier transform infrared spectrometer ( Figure 1 ), as can be seen in the figure, 797cm -1 The peak at 1030cm is the characteristic peak of the bending vibration of the benzene ring. -1 With 1240cm -1 Nearby is the stretching vibration characteristic peak of CO on the spiro ring; the range of 1255-1380cm-1 is the vibration absorption peak of the substituent on the indoline ring; 1450, 1600, 2210cm -1 The range is the characteristic peak of the stretching vibration of the cyano group of the naphthalene ring, 3040cm -1 Nearby is the characteristic peak of CH stretching vibration.

[0051] Elemental analysis: Calculated: C 78.18, H 5.28, N 11.72, Found: C 78.10, H 5.35, N 11.74.

[0052] 2. Polyurethane acrylate prepolymer

[0053]

[0054] 450 g of toluene diisocyanate (TDI) and 9 kg of ethyl acetate solvent were added to 850 g of polyethylene adipate, and 5 g of dibutyltin dilaurate was slowly added. The mixture was dripped for 25 min. The mixture was protected by nitrogen and the temperature was controlled at 65 ° C for 85 min. 15 g of 1,4-butanediol and 12 g of 3-methyl-1,5-pentanediol were added in sequence and the reaction lasted for 90 min. 230 g of hydroxyethyl acrylate (HEA) was added, the temperature was lowered to 50 ° C, and the reaction lasted for 5 hours and 8 minutes. The measured value was 2236 cm -1 The stretching vibration absorption peak of -NCO disappears, and the solvent is evaporated to obtain the polyurethane acrylate prepolymer.

[0055] Example 1: Preparation of photochromic nanocomposite microspheres, multi-color coating liquid and filter lens

[0056] (I) Preparation of photochromic nanocomposite microspheres:

[0057] 1. Preparation of titanium oxide hydrosol: Take 150g TiCl4 and add it to 1500ml pure water, add dilute H2SO4 until the solution is transparent, then add 25wt% NaOH aqueous solution, adjust the pH value to 9, heat to 50℃ after the precipitate is precipitated, add acid to adjust the pH value to 5, and after the precipitate is dissolved, obtain titanium oxide hydrosol.

[0058] 2. Preparation of photochromic color-forming body solution: 15 g of spirooxazine photochromic compound (IV) and 1000 g of ethanol were prepared into a photochromic solution.

[0059] 3. Preparation of core-shell photochromic nanospheres: Add the photochromic color former solution prepared in step 2 to the titanium oxide colloid, and add 5.5 g of thioglycolic acid and 3.5 g of sodium dodecylbenzene sulfonate, stir for 35 min, cool to room temperature, filter and collect the precipitate, wash, and dry to obtain core-shell nano titanium oxide photochromic microspheres. The yield is 69%.

[0060] Figure 2 This is a transmission electron microscope (TEM) image of titanium oxide modified nanomaterials. It can be seen from the image that the appearance is spherical, composed of TiO2 nanocrystals agglomerated, and the light-colored outer layer is the shell formed by the spirooxazine color-changing compound and the surfactant, which is displayed as a white bright circle in the transmission electron microscope photo. Through the Scherrer formula (D = K / βcosθ) and Zeta potential analysis and calculation, it is concluded that the outer diameter of the composite microsphere is 65nm, of which the diameter of the titanium oxide nanosphere is 28nm, the thickness of the middle layer is 9.5nm, and the thickness of the shell is 9nm.

[0061] Figure 3 The XRD diffraction patterns of the nano-titanium oxide photochromic microspheres and pure nano-titanium oxide prepared in Example 1 show that the nano-composite microspheres have strong diffraction peaks at 2θ of 25.2°, 37.6°, 48.0°, 53.8°, 62.6°, 68.6°, 70.3° and 75.3°, which are consistent with the characteristic diffraction of TiO2 anatase phase, indicating that the organic matter loaded on the surface has not changed the nano-TiO2 crystal phase, thereby determining that the TiO2 structure is orthorhombic anatase type.

[0062] (II) Preparation of colorful color-changing coating liquid:

[0063] 1. Prepare the first colorful color-changing coating liquid: take 15g of the photochromic nanospheres prepared in the above steps, 38g of ethoxyphenol acrylate, and 0.6g of D90 defoamer, add them to 420g of polyurethane acrylate prepolymer, stir at room temperature for 30 minutes, and obtain component A; weigh 10g of 2-hydroxy-2-methyl-1-phenylacetone 1173 and add it to the above component A, mix evenly, and obtain the first colorful color-changing coating liquid.

[0064] 2. Prepare the second multi-color color-changing coating liquid: take 50 g of the first multi-color color-changing coating liquid prepared in the above steps, add 1.9 g of ethoxyphenol acrylate, and obtain the second multi-color color-changing coating liquid.

[0065] (III) Preparation of multi-color color-changing filter lenses:

[0066] The first multi-color coating liquid was filtered and degassed through a filter membrane, and then spin-coated onto the surface of the acrylic optical lens at a speed of 2500 rpm. The coated sheet was then placed under a light intensity of 200 mW / cm 2 The UV-LED light curing machine is used to irradiate for 61 seconds. Then, the second multi-color-changing coating liquid is coated on the cured coating by the same coating and curing operation method to obtain a multi-color-changing anti-blue light lens.

[0067] Example 2: Preparation of photochromic nanocomposite microspheres, multi-colored color-changing coating liquid and filter lens

[0068] (I) Preparation of photochromic nanocomposite microspheres:

[0069] 1. Preparation of titanium oxide hydrosol: Take 150g TiCl4 and add it to 1350ml pure water, add dilute H2SO4 until the solution is transparent, then add 25wt% NaOH aqueous solution, adjust the pH value to 9.5, heat to 50℃ after the precipitate is precipitated, add acid to adjust the pH value to 5.5, and after the precipitate is dissolved, obtain titanium oxide hydrosol.

[0070] 2. Preparation of photochromic color-forming body solution: 15 g of spiropyran photochromic compound (compound of formula I) and 1200 g of ethanol were prepared into a photochromic solution.

[0071] 3. Preparation of core-shell photochromic nanospheres: Add the photochromic solution prepared in step 1 to the titanium oxide colloid, and add 4.5 g of thioglycolic acid and 4 g of sodium dodecylbenzene sulfonate, stir for 35 min, cool to room temperature, collect the precipitate by filtration, wash, and dry to obtain core-shell nano-titanium oxide photochromic microspheres.

[0072] (II) Preparation of colorful color-changing coating liquid:

[0073] 1. Prepare the first colorful color-changing coating liquid: take 15g of the photochromic nanospheres prepared in the above steps, 40g of ethoxyphenol acrylate, and 0.6g of D90 defoamer, add them to 400g of polyurethane acrylate prepolymer, stir at room temperature for 30 minutes, and obtain component A; weigh 11g of 2-hydroxy-2-methyl-1-phenylacetone 1173 and add it to the above component A, mix evenly, and obtain the first colorful color-changing coating liquid.

[0074] 2. Prepare the second multi-color-changing coating liquid: take 50 g of the first multi-color-changing coating liquid prepared in the above steps, add 1.8 g of ethoxyphenol acrylate, and obtain the second multi-color-changing coating liquid.

[0075] (III) Preparation of multi-color color-changing filter lenses:

[0076] The first multi-color coating liquid was filtered and degassed through a filter membrane, and then spin-coated onto the surface of the optical CR39 lens at a speed of 2500 rpm. The coated sheet was then placed under a light intensity of 200 mW / cm 2 The UV-LED light curing machine is used to irradiate for 63 seconds. Then, the second multi-color-changing coating liquid prepared in Example 1 is coated on the cured coating by the same coating and curing operation method to obtain a multi-color-changing blue light protection lens.

[0077] Example 3: Preparation of photochromic nanocomposite microspheres, multi-colored color-changing coating liquid and filter lens

[0078] (I) Preparation of photochromic nanocomposite microspheres:

[0079] 1. Preparation of titanium oxide hydrosol: Take 150g TiCl2 and add it to 1800ml pure water, add dilute H2SI4 until the solution is transparent, then add 25wt% NaOH aqueous solution, adjust the pH value to 9.5, heat to 50℃ after the precipitate is precipitated, add acid to adjust the pH value to 5.5, and after the precipitate is dissolved, obtain titanium oxide hydrosol.

[0080] 2. Preparation of photochromic color-forming body solution: 15 g of spiropyran photochromic compound (compound of formula II) and 950 g of ethanol were prepared into a photochromic solution.

[0081] 3. Preparation of core-shell photochromic nanospheres: Add the photochromic solution prepared in step 1 to titanium oxide colloid, and add 6 g of thioglycolic acid and 4 g of sodium dodecylbenzene sulfonate, stir for 35 min, cool to room temperature, collect the precipitate by filtration, wash, and dry to obtain core-shell nano-titanium oxide photochromic microspheres.

[0082] (II) Preparation of colorful color-changing coating liquid:

[0083] 1. Prepare the first colorful color-changing coating liquid: take 15g of the photochromic nanospheres prepared in the above steps, 45g of ethoxyphenol acrylate, and 0.6g of D90 defoamer, add them to 380g of polyurethane acrylate prepolymer, stir at room temperature for 30 minutes, and obtain component A; weigh 10g of 2-hydroxy-2-methyl-1-phenylacetone 1173 and add it to the above component A, mix evenly, and obtain the first colorful color-changing coating liquid.

[0084] 2. Prepare the second multi-color-changing coating liquid: take 50 g of the first multi-color-changing coating liquid prepared in the above steps, add 1.8 g of ethoxyphenol acrylate, and obtain the second multi-color-changing coating liquid.

[0085] (III) Preparation of multi-color color-changing filter lenses:

[0086] The first multi-color coating liquid was filtered and degassed by a filter membrane, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coated sheet was then placed under a light intensity of 200 mW / cm 2 The UV-LED light curing machine is used to irradiate for 62 seconds. Then, the second multi-color-changing coating liquid prepared in Example 2 is coated on the cured coating using the same coating and curing operation method to obtain a multi-color-changing blue light-proof lens.

[0087] Example 4: Preparation of photochromic nanocomposite microspheres, multi-colored color-changing coating liquid and filter lens

[0088] (I) Preparation of photochromic nanocomposite microspheres:

[0089] 1. Preparation of titanium oxide hydrosol: Take 150g TiCl4 and add it to 1650ml pure water, add dilute H2SO4 until the solution is transparent, then add 25wt% NaOH aqueous solution, adjust the pH value to 9.5, heat to 50℃ after the precipitate is precipitated, add acid to adjust the pH value to 5.5, and after the precipitate is dissolved, obtain titanium oxide hydrosol.

[0090] 2. Preparation of photochromic color-forming body solution: 15 g of naphthopyran photochromic compound (compound of formula III) and 1350 g of ethanol were prepared into a photochromic solution.

[0091] 3. Preparation of core-shell photochromic nanospheres: Add the photochromic solution prepared in step 1 to the titanium oxide colloid, and add 6 g of thioglycolic acid and 5 g of sodium dodecylbenzene sulfonate, stir for 35 min, cool to room temperature, collect the precipitate by filtration, wash, and dry to obtain core-shell nano-titanium oxide photochromic microspheres.

[0092] (II) Preparation of colorful color-changing coating liquid:

[0093] 1. Prepare the first colorful color-changing coating liquid: take 15g of the photochromic nanospheres prepared in the above steps, 50g of ethoxyphenol acrylate, and 0.6g of D90 defoamer, add them to 440g of polyurethane acrylate prepolymer, stir at room temperature for 30 minutes, and obtain component A; weigh 10g of 2-hydroxy-2-methyl-1-phenylacetone 1173 and add it to the above component A, mix evenly, and obtain the first colorful color-changing coating liquid.

[0094] 2. Prepare the second multi-color color-changing coating liquid: take 50 g of the first multi-color color-changing coating liquid prepared in the above steps, add 1.9 g of ethoxyphenol acrylate, and obtain the second multi-color color-changing coating liquid.

[0095] (III) Preparation of multi-color color-changing filter lenses:

[0096] After filtering and degassing the first multi-color-changing coating liquid through a filter membrane, the first multi-color-changing coating liquid was spin-coated onto the surface of the optical polyurethane lens at a speed of 2500 rpm, and then the coating sheet was placed under a UV-LED light curing machine with a light intensity of 200 mW / cm2 for 60 seconds. Subsequently, the second multi-color-changing coating liquid prepared in Example 3 was coated on the cured coating using the same coating and curing operation method to obtain a multi-color-changing blue light protection lens.

[0097] Example 5: Preparation of multi-color color filter lenses

[0098] The first multi-color coating liquid prepared in Example 1 was filtered and degassed by a filter membrane, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2 The second multi-color-changing coating liquid prepared in Example 4 was coated on the coating layer by the same coating and curing operation method. After the coating layer was completely cured, a multi-color-changing blue light-proof lens was obtained.

[0099] Example 6: Preparation of multi-color color filter lenses

[0100] The first multi-color coating liquid prepared in Example 1 was filtered and degassed by a filter membrane, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2 The second multi-color-changing coating liquid prepared in Example 3 was coated on the coating layer by the same coating and curing operation method. After the coating layer was completely cured, a multi-color-changing blue light-proof lens was obtained.

[0101] Example 7: Preparation of multi-color color filter lenses

[0102] The first multi-color coating liquid prepared in Example 1 was filtered and degassed by a filter membrane, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2 The second multi-color-changing coating liquid prepared in Example 2 is coated on the coating layer by the same coating and curing operation method. After the coating layer is completely cured, a multi-color-changing blue light-proof lens is obtained.

[0103] Example 8: Preparation of multi-color color filter lenses

[0104] The first multi-color coating liquid prepared in Example 4 was filtered and degassed, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2The second multi-color-changing coating liquid prepared in Example 3 was coated on the coating layer by the same coating and curing operation method. After the coating layer was completely cured, a multi-color-changing blue light-proof lens was obtained.

[0105] Example 9: Preparation of multi-color color filter lenses

[0106] The first multi-color coating liquid prepared in Example 1 was filtered and degassed by a filter membrane, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2 The first multi-color coating liquid prepared in Example 3 is coated on the coating layer by the same coating and curing operation method, and then the second multi-color coating liquid prepared in Example 4 is coated after curing, and the coating layer is completely cured to obtain a multi-color anti-blue light lens.

[0107] Example 10: Preparation of multi-color color filter lenses

[0108] The first multi-color coating liquid prepared in Example 4 was filtered and degassed, and then spin-coated onto the surface of the optical PC substrate at a speed of 2500 rpm. The coating sheet was then placed under a light intensity of 200 mW / cm 2 The second multi-color-changing coating liquid prepared in Example 2 is coated on the coating layer by the same coating and curing operation method. After the coating layer is completely cured, a multi-color-changing blue light-proof lens is obtained.

[0109] Example 11: Preparation of colorful color-changing coating liquid and filter lens

[0110] 1. Prepare a first colorful color-changing coating liquid: take 5 g of the photochromic nanospheres prepared in Example 1, 10 g of the photochromic nanospheres prepared in Example 3, 45 g of ethoxyphenol acrylate, and 0.6 g of D90 defoamer, add them to 380 g of polyurethane acrylate prepolymer, stir at room temperature for 30 minutes, and obtain component A; weigh 10 g of 2-hydroxy-2-methyl-1-phenylacetone 1173 and add it to the above component A, mix evenly, and obtain a first colorful color-changing coating liquid.

[0111] 2. Prepare the second multi-color-changing coating liquid: take 50 g of the first multi-color-changing coating liquid prepared in step 1 above, add 1.8 g of ethoxyphenol acrylate, and obtain the second multi-color-changing coating liquid.

[0112] 3. Preparation of multi-color filter lenses: After filtering and degassing the first multi-color coating liquid through a filter membrane, spin-coat it onto the surface of the optical PC substrate at a speed of 2500 rpm, and then place the coating sheet under a light intensity of 200 mW / cm 2The second multi-color-changing coating liquid prepared in step 2 is coated on the coating layer by the same coating and curing operation method. After the coating layer is completely cured, a multi-color-changing blue light-proof lens is obtained.

[0113] Example 12: Photochromic response test on multi-color color filter lens

[0114] (I) Photochromic response value test

[0115] Testing steps and methods: Light transmittance tV of the tested sample in the faded state o The ratio of the light transmittance tV1 in the color-changing state after 15 minutes of illumination, that is, spectral response value = tV0 ÷ tV1, is used to determine the photochromic response value of the sample under test. The solar simulator is used as an excitation light source with an ultraviolet lamp of λ = 365nm and irradiated at a distance of 6cm. The test results are shown in Table 1.

[0116] (II) Photochromic spectral response time detection

[0117] Detection steps and methods: Place Examples 1-11 and the prepared filter lenses in a test box respectively, turn on the solar simulator light source, and record the time required for the lenses to change from colorless to colored; turn off the simulated light source after 15 minutes of irradiation, and record the time required for the lenses to return to a colorless state from colored. The detection results are shown in Table 1.

[0118] Table 1 Detection of photochromic response values ​​of lenses

[0119]

[0120]

[0121] The test results show that the colorful color-changing filter lens containing photochromic nanocomposite microspheres manufactured by the present invention can achieve the change and fade of multiple colors according to the spectral response time and speed (sensitivity) of different types of photochromic compounds, so that the change and fading process presents a variety of color changes before and after, ensuring the color change and visual effect.

[0122] Example 13: Optical performance test of multi-color filter lenses

[0123] The light transmittance (T / %) performance of the filter lenses prepared in Examples 1-11 was tested respectively, using a UV-8000 ultraviolet-visible photometer produced by Shanghai Yuanxi Instrument Co., Ltd.; representative wavelengths of different spectral regions were selected for testing, and the test results are listed in Table 2. Figure 4 This is a comparison spectrum of the multi-color-changing blue light protection lens prepared in Example 1 before and after irradiation.

[0124] Table 2 Sample light transmittance test results Unit: T%

[0125]

[0126]

[0127] The test results show that the colorful color-changing filter lens containing photochromic nanocomposite microspheres manufactured by the present invention can not only change color in sunlight to protect against strong light and ultraviolet rays, but also protect against blue light below 435nm indoors, achieving the performance of all-weather protection against ultraviolet rays and short-wave blue light in different light and dark environments.

[0128] Example 14: Absorbance and multi-color performance test of photochromic nanocomposite microspheres

[0129] (I) Absorption spectrum detection of photochromic nanocomposite microsphere solution

[0130] Detection steps: Take 0.45g of each photochromic nanocomposite microsphere prepared in Examples 1-4, add 5ml of ethanol solvent respectively, pour the mixed liquid into multiple glass beakers containing 50ml of methyl methacrylate monomer, mark IV-1, I-1, II-1 and III-1 on the beakers, respectively, put them in a xenon lamp test box for ultraviolet light irradiation detection and visible light irradiation detection, irradiate with ultraviolet lamp at room temperature for 120S, the distance between the solution and the light source is 12CM, and record the difference between the absorption spectrum before irradiation and the absorption spectrum after irradiation. The results are shown in Table 3. Figure 5 This is the absorbance spectrum of IV-1 solution. The difference in the absorption spectrum shows that the photochromic response effect is obvious.

[0131] Table 3 Absorbance and absorption spectrum difference of sample solution in the embodiment

[0132]

[0133] (II) Spectral response performance test of photochromic nanocomposite microsphere solution

[0134] Testing steps: Take 6g, 6g and 5g of the IV-1, II-1 and III-1 solutions prepared in Example 14 respectively, mix the solutions and place them under a xenon lamp for ultraviolet irradiation, record the color change of the mixed solution and the required time; turn off the simulated light source and record the fading color change and time. The results are shown in Table 4. Figure 6 Take a photo with your phone to record the color change process.

[0135] Table 4 Spectral response of sample solutions in the examples

[0136]

[0137] Conclusion: The present invention shows that the prepared photochromic nanocomposite microspheres have sensitive photochromic response by detecting the change of absorbance value before and after color change, and the whole color change and fading process is rich in color.

Claims

1. A method for preparing a colorful color-changing material, characterized in that: The method comprises the following steps: a. Preparation of titanium oxide hydrosol: Adding H2SO4 aqueous solution to a soluble titanium salt aqueous solution with a concentration of 0.1 to 1 mol / L until the solution becomes transparent, then adding a 15 to 30 wt% NaOH aqueous solution with a pH value between 7 and 11, and gradually precipitating; heating to 30° to 70°C, adding acid to dissolve the precipitate, and the pH value is between 4 and 7 to obtain a titanium oxide hydrosol; b. Preparation of photochromic color former solution: Adding the photochromic compound into an alcohol solvent, the photochromic compound and the solvent are prepared in a mass ratio of 1:(50-120) to obtain a photochromic color-forming body solution; The color-changing compound is selected from one of the following compounds: c. Preparation of core-shell photochromic nanocomposite microspheres: The photochromic color-forming body solution prepared in step b is added to the titanium oxide hydrosol, and a surfactant is added, wherein the mass ratio of the photochromic compound, the soluble titanium salt and the surfactant is 1:(5-17):(0.5-0.9), and the surfactant is at least one of stearic acid, alkyl glucoside, sodium dodecylbenzene sulfonate, fatty acid glyceride, polysorbate, lauroyl glutamic acid, thioglycolic acid, mercaptopropionic acid and α-mercaptoglycerol; stirring for 20-40 minutes, cooling to room temperature, allowing the reaction solution to precipitate by layers, filtering and collecting the precipitate, washing, and drying to obtain titanium oxide nanoparticles containing photochromic compounds modified by surfactant ligands.

2. The preparation method according to claim 1, characterized in that The soluble titanium salt is one of titanium dichloride, titanium tetrachloride, titanium sulfite and titanyl sulfate.

3. The preparation method according to claim 1 or 2, characterized in that: The solvent is at least one of methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, and hexylene glycol.

4. The preparation method according to claim 3, characterized in that: The solvent is at least one of methanol, ethanol and isopropanol.

Citation Information

Patent Citations

  • Blue light cut nano compound resin material, lens and preparation method thereof

    CN103980643A

  • Blue color weakness correction lens and preparation method thereof

    CN114031706A

  • Encapsulated photochromic microsphere as well as preparation method and application thereof

    CN115011327A

  • Oil dispersion of photochromic titanium oxide, oleophilic titanium oxide powder, method for producing the same, film-forming or film composition obtained from the dispersion and composition containing the same

    JP2001200195A

  • Method for preparing a photochromic polyurethane latex and application to ophthalmic optics

    US20040012002A1